Discrepancy in scientific authority and media visibility of climate change scientists and contrarians - Alexander Michael Petersen (Nature Portfolio, 2019)
The role of climate change (CC) contrarians is neglected in climate change communication studies. Here the authors used a data-driven approach to identify CC contrarians and CC scientists and found that CC scientists have much higher citation impact than those for contrarians but lower media visibility.